2018
DOI: 10.4103/ijem.ijem_414_16
|View full text |Cite
|
Sign up to set email alerts
|

A prospective, observational study of osteoporosis in men

Abstract: Context:The number of men afflicted with osteoporosis is unknown.Aims:This study aims to determine the prevalence of osteoporosis in men.Settings and Design:This was a prospective, observational study.Subjects and Methods:A total of 200 male attendants of patients attending endocrine outpatient department and who were >55 years were recruited for the study. All the patients with osteopenia and osteoporosis were advised lifestyle interventions, supplementation with calcium carbonate (1000–1500 mg/day) and 25-hy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…Some previous studies demonstrated that hypogonadism was the cause of male osteoporosis (6.9%–58%) [ 42 , 43 , 44 , 45 , 46 , 47 ] ( Table 1 ). However, these studies are limited by their small sizes and various potential biases.…”
Section: The Relationship Between Hypogonadism and Bmd In Humansmentioning
confidence: 99%
“…Some previous studies demonstrated that hypogonadism was the cause of male osteoporosis (6.9%–58%) [ 42 , 43 , 44 , 45 , 46 , 47 ] ( Table 1 ). However, these studies are limited by their small sizes and various potential biases.…”
Section: The Relationship Between Hypogonadism and Bmd In Humansmentioning
confidence: 99%
“…In aging population, morbidity and mortality from hip fractures are higher in men than in women with fatality rates, among over 75 years is 20.7% in men vs. 7.5% in women [7]. The causes of osteoporosis in men are relative to hormonal, genetics, environmental, other specific disease factors, and along 50% of men with secondary osteoporosis [6,8]. The three primary causes of secondary osteoporosis in men are glucocorticoid excess, hypogonadism, and alcohol abuse.…”
Section: Introductionmentioning
confidence: 99%
“…[1] Its deficiency leads to secondary hyperparathyroidism, increased bone turnover, and bone loss, predisposing individuals to osteoporosis and osteoporotic fractures. [23] The optimal serum level of vitamin D required for maintenance of bone health. [4] However, the appropriate dosage for replacement therapy is still debatable.…”
Section: Introductionmentioning
confidence: 99%